2001
DOI: 10.1021/jp002531f
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Forces between Hydroxypropylcellulose Polymers:  Temperature Favored Assembly and Salt Exclusion

Abstract: The thermodynamic forces between hydroxypropylcellulose (HPC) molecules at close separation have been measured using the osmotic stress method coupled with X-ray scattering. Two force regimes are apparent:  a very short ranged, temperature insensitive force that dominates interactions within the last 2.5 Å separation and a longer-ranged force that varies exponentially vs distance with a decay length of about 3−4 Å. The longer-ranged force characteristics are strikingly similar to those found for many other mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 46 publications
4
63
2
Order By: Relevance
“…Figure 4 shows the intensity of 90° scattered light as a function of temperature for dilute HPC (~100 µg/ml) in water and in 1 m proline. The midpoint transition without added osmolyte occurs at ~ 42 °C as has been observed by many others (13). Proline causes a significant decrease in the cloud-point temperature.…”
Section: The Effect Of Osmolytes On Hpc Precipitationsupporting
confidence: 73%
See 2 more Smart Citations
“…Figure 4 shows the intensity of 90° scattered light as a function of temperature for dilute HPC (~100 µg/ml) in water and in 1 m proline. The midpoint transition without added osmolyte occurs at ~ 42 °C as has been observed by many others (13). Proline causes a significant decrease in the cloud-point temperature.…”
Section: The Effect Of Osmolytes On Hpc Precipitationsupporting
confidence: 73%
“…We have previously determined the transition entropy from the temperature dependence of forces between HPC polymers (13). ΔΓ w can be calculated by integrating equation (3).…”
Section: Thermodynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By solution casting method these polymer blend films were also prepared and their miscibility studied using FTIR, DSC, X-RD, and SEM techniques. The compatibility of these polymer blends is discussed and it is concluded that the presence of hydrogen bonding groups [20,21] in these two polymers is responsible for the polymerpolymer interactions [22]. These results are presented here.…”
Section: International Journal Of Carbohydrate Chemistrymentioning
confidence: 73%
“…Figure 23 shows the ͑hypothetical͒ complexity of Nafion-like random copolymer membranes at atomic to macroscopic scales. Attempts to model structure and dynamics of such membranes at these scales have thus far met with limited success ͑Jang et al., 2004;Kreuer et al, 2004;Blake et al, 2005͒. The morphology assumed by uncharged diblock copolymers reflects, to a good approximation, only the volume fraction of the two components ͑Khandpur et Bates and Fredrickson, 1999͒. The excludedvolume and component-specific affinity effects of inorganic nanoparticles on diblock copolymer morphology, chemical and mechanical stability have been clearly demonstrated for the simpler case of nanoparticleguided self-assembly of uncharged block copolymers ͑Balazs et al, 2006͒.…”
Section: Proton Exchange Membranes For Hydrogen Fuel Cellsmentioning
confidence: 99%